Communication of behaviour change interventions: Can they be recognised from written descriptions?. Issue 6 (3rd June 2018) - Johnston, Marie; Johnston, Derek; Wood, Caroline E.; Hardeman, Wendy; Francis, Jill; Michie, Susan
Abstract : Objective: Communication of the content of a behaviour change intervention (BCI) involves clear description followed by appropriate recognition and interpretation. We investigated accuracy of recognition of BCI descriptions and the effects of training in the behaviour change taxonomy BCTTv1. Methods: Materials were 166 written descriptions of two BCIs previously written by 166 separate writers after viewing a video of the BCI. Each of the current participants (12 naïve and 12 trained in BCTTv1) was presented with a random sample of the written descriptions and asked to form groups of descriptions they judged to be describing the same intervention. For each participant, we assessed the number of groupings of BCI descriptions, their purity (containing only one BCI) and their differentiation (having a dominant BCI). Results: All except one participant classified the descriptions into more than two groupings. Naïve participants created significantly more groupings, fewer 'pure' groupings and less differentiated groupings (all Mann –Whitney p  < .05). Conclusions: Written communications of BCI contents may not be recognised and interpreted adequately to support implementation. BCT taxonomy training may lead to some progress in interpreting the active content of interventions but, based on this limited study, further progress is needed if BCIs for accurate implementation.